THE IMPLICATIONS OF REGIONAL COMPETITIVENESS ON REGIONAL DEVELOPMENT POLICY AND ECONOMIC COHESION - PIRVU, Ramona; RADOI, Ionut Mihai (Theoretical and Practical Research in Economic Fields, 2019)
Starting from the calculation pattern of the regional competitiveness in Romania, proposed by GEA in 2007, we proposed to draft a hard matrix where we could draft a comparative analysis of the evolution of the competitiveness of the regions in Romania regarding the values registers in 2017 as opposed to 2007. The research presented takes into consideration the available regional indicators on the level of Romania as well as: the GDP per capita, the growth rate of the gross added value, the share of the gross GDP, the employment rate, the index of the life expectancy, the population with the risk of poverty or social exclusion, research-development expenses in GSP, employees in research-development from the total employed population, tertiary education in research-development, innovative enterprises in total enterprises and so on. We also selected a linear pattern based on 3 factors according to which the regional competitiveness will be analysed that is the economic factors, the social factor and the technologic factor. The data used were collected from the existing database on the level of the national Statistics Institute and on the international Eurostat level .